A case study of promoting continuous improvement in school leadership through digital self-assessment tools: MySkillScan / Goh Kok Ming and Mahaliza Mansor - Goh, Kok Ming; Mansor, Mahaliza (Universiti Teknologi MARA, Kedah, 2023)
Self-assessment is an essential tool for educational leaders as it allows them to identify their strengths and areas for improvement. Educational leaders who engage in self-assessment gain valuable insights into their competencies and skills, which can help them develop strategies for enhancing their performance. This involves analyzing different aspects of educational management, such as planning, understanding student and teacher psychology, self-organization, time management, coordinating organizational activities, the impact on student learning, motivation and development of teachers, team building, and leadership skills. To evaluate the competency level of educational leaders, an innovative self-assessment tool has been developed, which includes five levels ranging from no experience to exceptional expertise. The tool presents an interactive spider-web visualization based on the leaders' responses, allowing them to assess their skills and competencies in various aspects of educational management. The tool has been quantitatively and qualitatively pilot-tested with a select group of ten leaders and proved effective in providing valuable insights into their skills and competencies, helping them identify areas for further development. There are three emerging themes , 1) self-awareness, 2) constructive feedback, and 3) meaningful interaction, to form a main theme that is continuous improvement based on the interview findings. In conclusion, this self-assessment tool can serve as a starting point for educational leaders to identify their strengths and weaknesses in this area, develop strategies for enhancing their skills, and ultimately improve overall educational outcomes. For further exploration, the tool can be considered for wider implementation in educational management practices.